Per una metodologia del protogiallo italiano: Problemi e proposte. (August 2019) - Facchi, Francesca
In the first systematic study about the Italian detective novel (1979), Loris Rambelli dates the beginnings of the genre to 1929, the publication year of the first of publisher Mondadori's 'Yellow Books' (Libri Gialli), the series of yellow-covered books which made the 'giallo' synonymous with a crime novel. Nonetheless, texts dealing with mysteries, criminals, police, trials and detection enthralled Italian readers from the 1850s on, complying with the modern dynamics of mass phenomena, contributing to the modern conception of the genre, and playing a crucial role in the culture and society of a recently unified Italy. Not conforming to a recognizable genre-structure, the pre-1929 period has been defined the "prehistory of Italian crime fiction" or protogiallo and has become a topic of academic interest only in recent years. The newness of the scholarship explains the methodological difficulties researchers have to face, such as the classification problem – it is very complex to establish common critical criteria for analyzing diverse materials such as feuilletons, novels, short stories and famous trials journals – and the objective delay in the development of the genre in Italy, especially compared to the British, American and French cases. Building on the recent line of investigation, this paper examines such critical issues in order to identify a methodological approach and a theoretical framework useful to study the prehistory of Italian crime fiction.